2020
DOI: 10.1093/humrep/deaa311
|View full text |Cite
|
Sign up to set email alerts
|

SARS-CoV-2 in first trimester pregnancy: a cohort study

Abstract: Study question Does maternal infection with SARS-CoV-2 in first trimester pregnancy have an impact on the fetal development as measured by nuchal translucency thickness and pregnancy loss? Summary answer Nuchal translucency thickness at the first trimester scan was not significantly different in pregnant women with versus without SARS-CoV-2 infection in early pregnancy and there was no significant increased risk of pregnancy … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
66
0
2

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 65 publications
(79 citation statements)
references
References 19 publications
4
66
0
2
Order By: Relevance
“…Single-cell transcriptomic data on single-nuclear RNA-sequencing from first-trimester placentas demonstrated that co-expression of ACE2 and TMPRSS2 is negligible at this stage (<1/10,000 cells) [21]. These findings could also explain the recent evidence showing no increase in early pregnancy loss in patients with SARS-CoV-2 infection [22,23]. Conversely, the viral receptors used by Cytomegalovirus, Zika virus and other viruses are highly expressed by human placental tissues [24].…”
Section: Discussionmentioning
confidence: 89%
“…Single-cell transcriptomic data on single-nuclear RNA-sequencing from first-trimester placentas demonstrated that co-expression of ACE2 and TMPRSS2 is negligible at this stage (<1/10,000 cells) [21]. These findings could also explain the recent evidence showing no increase in early pregnancy loss in patients with SARS-CoV-2 infection [22,23]. Conversely, the viral receptors used by Cytomegalovirus, Zika virus and other viruses are highly expressed by human placental tissues [24].…”
Section: Discussionmentioning
confidence: 89%
“…22 Furthermore, SARS-CoV-2 infection does not alter the nuchal translucency or any of the other ultrasound signs used to screen for Trisomy 21 in the first trimester of pregnancy. [23][24] Although encouraging, data from early pregnancy are still limited and mostly refer to non-hospitalized and/or asymptomatic women. Finally, no specific anomaly has been reported to be associated with the infection.…”
Section: Which Are the Fetal Risks Of Sars-cov-2 Infection?mentioning
confidence: 99%
“…Some reports suggested that COVID-19 in pregnancy is analogous to the disease experienced in the general population [ 1 , 4 , 15 – 17 ]. From Denmark, a cohort study did not find ultrasound evidence of fetal compromise during first trimester infections nor increased pregnancy loss [ 18 ]. The latter was supported by comparative studies in which infected pregnant patients were compared to either non-infected pregnancies, non-pregnant infected females in the community, or patients with alternative virus infections [ 19 – 24 ].…”
Section: Maternal Infection With Sars-cov-2mentioning
confidence: 99%
“…Similar findings were also noted after another putative vertical transmission [ 146 ]. During the first trimester infections, maternal SARS-CoV-2 antibody was found among some women but not consistently so [ 18 ]. Edlow et al provided findings of cord bloods harboring IgG antibodies to both the viral receptor binding domain and nucleocapsid for a small majority [ 73 ].…”
Section: Maternal Infection With Sars-cov-2mentioning
confidence: 99%